Rare blood transfusion hazard-TRALI: a case report - Bhattarai, Prerana; Shrestha, Junu; Upreti, Dipesh (Journal of Chitwan Medical College, 2022)
Transfusion related acute lung injury is a rare life-threatening complication of blood transfusion. The diagnosis is done clinically as there are no distinguishing biomarkers. We report a case of 25 years old female with six weeks of gestation with ruptured ectopic, who presented to the emergency department with acute abdominal pain. She underwent emergency laparotomy and received two units of blood transfusion post-operatively. Eight hours after surgery and six hours following blood transfusion, the patient developed fever (1010 F), tachycardia (> 140 bpm) and respiratory distress (SPO2: <80%, Respiratory rate: >30 per minute). The diagnosis of transfusion related acute lung injury was made and managed accordingly in Intensive Care Unit. Being a potentially life-threatening complication of the blood transfusion, early clinical diagnosis and further management is crucial to prevent fatal outcome.